Analisis Film “Home Sweet Loan” Terkait Isu Sosial Sandwich Generation menggunakan Teori Semiotika John Fiske - Athella Inaia Dhia Haretri; Dwi Puji Prabowo (Lembaga Pengembangan Kinerja Dosen, 2025)
Film is a communication medium that has the power to convey social messages to audiences through narrative and visuals. One of the social phenomena currently being extensively discussed is the issue of the sandwich generation, which is the first topic in the